The ubiquitin ligase Pellino1 targets STAT3 to regulate macrophage-mediated inflammation and tumor development - Soeun Hwang; Junhee Park; Seo-Young Koo; Si-Yeon Lee; Yunju Jo; Dongryeol Ryu; Heounjeong Go; Chang-Woo Lee (Nature Communications)
Abstract Receptor-mediated signaling could be modulated by ubiquitination of pathway intermediates, but the role of such modification in the pathogenesis of inflammation and inflammation-related cancer is lesser known. The ubiquitin ligase Pellino1 has been shown to modulate immune signals by enabling various immune cells to respond to their receptor signals effectively. Here, we show that Pellino1 levels are elevated in patients with colitis, patients with colitis-associated colon cancer (CAC), and murine models of these conditions. In a monocyte-specific Pellino1 knock-out mouse model, we find reduced macrophage migration and activation, leading to attenuated development of colitis and CAC in male mice. Mechanistically, Pellino1 targets STAT3 for lysine 63-mediated ubiquitination, resulting in pathogenic activation of STAT3 signaling. Taken together, our findings reveal a macrophage-specific ubiquitination signaling axis in colitis and CAC development and suggest that Pellino1 is a potential candidate for treating chronic inflammation and inflammation-related cancer.